Adherens, tight, and gap junctions in ependymal cells: A systematic review of their contribution to CSF-brain barrier - Serra, Riccardo; Simard, J. Marc (Frontiers in Neurology, 2023)
The movement of fluids and solutes across the ependymal barrier, and their changes in physiologic and disease states are not well understood. Previous studies have suggested trans-ependymal flow as a path of CSF secretion and reabsorption. The role that tight junctions, adherens junctions and gap junctions play in CSF and solute flow movement across the ependyma remains to be fully characterized. We systematically reviewed original research articles dealing with ependymal intercellular junctions. Reviews, opinion papers, and abstracts were excluded. Research conducted on tissue samples, cell lines, CSF and animal models was considered. In this review, we collect, summarize, and interpret the current literature on this topic. A total of 35 novel articles treating tight, adherens and gap junctions of the ependyma were included, spanning from 1960 to 2022. The findings of this review point towards a central and not yet fully characterized role of the ependymal lining ultrastructure in fluid flow interactions in the brain. Tight junctions circumferentially line the apical equator of ependymal cells, changing between embryonal and adult life in several rodent models, shaping fluid and solute transit in this location. Further, adherens and gap junctions appear to have a pivotal role in several forms of congenital hydrocephalus. Further advances may provide opportunities for medical management of CSF disorders, potentially allowing for tuning of CSF secretion and absorption. Beyond hydrocephalus, stroke and trauma, this information has relevance for metabolite clearance and drug delivery, with the potential to affect many patients with a variety of neurological disorders.